Adjectives of completeness as maximizers of event nominalizations - Masià, Melania S. (Borealis – An International Journal of Hispanic Linguistics, 2017)
Aspectual modifiers that have adverbial and adjectival counterparts are an important source of information for researching lexical aspect in the nominal domain. One class of such modifiers are adverbs of completeness (completamente 'completely', totalmente 'totally'), which are maximizers when modify adjectives, and their correspondent adjectives (completo 'complete', total 'total'). This paper addresses the inheritance of aspectual features and its relation to degree in event nominalizations of incremental theme verbs (traduccción 'translation', destrucción 'destruction') through the analysis modification by adjectives of completeness in Spanish. The proposal combines a syntactic account of deverbal nominalizations with a scalar approach to aspect. Adjectives of completeness are argued to be aspectual modifiers, with a contribution equivalent to that of their adverbial counterparts both in the verbal and in the adjectival domain, establishing thus a parallelism between degree modification of adjectives, verbs and nominals.